Endothelial cell-modified BMSC-GT/PCL nanofiber membrane sheet constructs promote bone tissue regeneration - Zhou, Qian; Wen, Mengnan; Zhang, Yiwu; Wang, Zhinan; Zhou, Guangdong; Liang, Xiaoqin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionBone defect repair remains a major challenge in modern medicine. Although bone marrow mesenchymal stem cells (BMSCs) possess multilineage differentiation potential, traditional BMSC constructs are often limited in clinical applications due to insufficient osteogenic differentiation efficiency and inadequate vascularization.MethodsThis study developed an innovative bone tissue engineering strategy by combining BMSCs with gelatin/polycaprolactone (GT/PCL) nanofiber membranes to form cell sheets, which were then modified with endothelial cells (ECs) on the surface. The sheets were subsequently rolled into three-dimensional scaffolds to systematically evaluate their osteogenic potential and underlying mechanisms.ResuiltsResults showed that electrospun GT/PCL nanofiber membranes exhibited uniform fiber structure (diameter 200–500 nm), successfully mimicking the microstructure of natural extracellular matrix. In vitro experiments demonstrated that after 14 days of culture, EC modification significantly enhanced the osteogenic differentiation of BMSCs compared to unmodified controls, with approximately 3-fold increase in ALP expression (p < 0.05) and 2.5-fold increase in angiogenic factor VEGF expression (p < 0.01). Subcutaneous implantation in nude mice revealed superior bone formation capability of EC-modified constructs at both 4 and 8 weeks: micro-CT analysis showed bone density reaching 350 mg/cm3, bone surface area approaching 400 mm2, and bone volume fraction of approximately 20%, significantly higher than control groups (p < 0.0001). Immunohistochemical evaluation further confirmed more mature trabecular bone structure and richer vascular networks in EC-modified groups.DiscussionMechanistic studies revealed that EC modification promoted bone regeneration through three key pathways: optimization of local vascular microenvironment for improved nutrient supply, activation of intercellular synergistic signaling pathways, and reconstruction of physiological bone tissue microenvironment. This study not only validates the application value of this composite strategy in bone tissue engineering but also provides important theoretical basis for developing novel bone regeneration solutions.